APSIC guide for prevention of Central Line Associated Bloodstream Infections (CLABSI). Issue 1 (December 2016) - Ling, Moi; Apisarnthanarak, Anucha; Jaggi, Namita; Harrington, Glenys; Morikane, Keita; Thu, Le; Ching, Patricia; Villanueva, Victoria; Zong, Zhiyong; Jeong, Jae; Lee, Chun-Ming
Abstract This document is an executive summary of the APSIC Guide for Prevention of Central Line Associated Bloodstream Infections (CLABSI). It describes key evidence-based care components of the Central Line Insertion and Maintenance Bundles and its implementation using the quality improvement methodology, namely the Plan-Do-Study-Act (PDSA) methodology involving multidisciplinary process and stakeholders. Monitoring of improvement over time with timely feedback to stakeholders is a key component to ensure the success of implementing best practices. A surveillance program is recommended to monitor outcomes and adherence to evidence-based central line insertion and maintenance practices (compliance rate) and identify quality improvement opportunities and strategically targeting interventions for the reduction of CLABSI.